A kidney discard decision strategy based on zero‐time histology analysis could lead to an unjustified increase in the organ turndown rate among ECD. (8th July 2021) - Luque, Yosu; Jamme, Matthieu; Aubert, Olivier; Roux, Arthur; Martinez, Frank; Amrouche, Lucile; Tinel, Claire; Galmiche, Louise; Duong Van Huyen, Jean‐Paul; Audenet, François; Legendre, Christophe; Anglicheau, Dany; et al.
Summary: The utility of zero‐time kidney biopsies (KB) in deciding to accept expanded criteria donor (ECD) kidneys remains controversial. However, zero‐time histology is one of the main causes for discarding kidneys in the United States. In a single‐centre study, we examined the utility and impact on outcome of the use of frozen section zero‐time KB among ECD. Ninety‐two zero‐time KB were analysed for accept/discard decision between 2005 and 2015 among ECD. 53% of kidneys were rejected after zero‐time KB analysis; there was no difference in individual clinical and biological data between accepted/rejected groups. However, histology of rejected kidneys showed more sclerotic glomeruli (20% vs. 8%; P  < 0.001), increased interstitial fibrosis (1.25 ± 0.12 vs. 0.47 ± 0.09; P  < 0.0001), more arteriosclerosis (2.14 ± 0.17 vs. 1.71 ± 0.11; P  = 0.0032) and arteriolar hyalinosis (2.15 ± 0.12 vs. 1.55 ± 0.11; P  = 0.0006). Using propensity score matching, we generated a group of 42 kidney allograft recipients who received a transplant matched for donor zero‐time histology and clinical characteristics with donors whose kidneys were rejected. Interestingly, their 1‐ and 5‐year graft survival and function were similar to the global cohort of ECD recipients. In conclusion, when performed, zero‐time KB was a decisive element for kidney discard decision. However, adverse zero‐time histology was not associated with poorer graft survival and kidney function among ECD. Abstract : When performed, zero‐time KB was a decisive element for kidney discard decision. However, adverse zero‐time histology was not associated with poorer graft survival and kidney function among ECD.